Prevalence of stunting and its determinants among children under five in 35 Sub-Saharan African countries (2011–2024): Insights from recent demographic health survey data using a generalized linear mixed-effects model with robust poisson regression - Abdulkerim Hassen Moloro; Kebede Gemeda Sabo; Kusse Urmale Mare; Beriso Furo Wengoro; Eshetu Elfios Endrias; Roda Mehadi Ibrahim; Teshager Dubie; Oumer Abdulkadir Ebrahim; Begetayinoral Kussia Lahole (PLoS ONE, 2026)
Background Despite efforts by initiatives like the World Bank’s ‘All Hands-on Deck’ and UNICEF’s programs to address stunting through multisectoral approaches, the burden of stunting remains alarmingly high in sub-Saharan Africa. This study utilized recent large-scale survey data from 35 SSA countries (2011–2024) to estimate the pooled prevalence of stunting and its determinants among children under 5 years of age. Key variables such as antenatal care visits, postnatal care, and maternal nutritional indicators, which previous studies did not account for, are incorporated into the analysis. Methods A secondary analysis was conducted using recent demographic and health survey data (2011–2024) from 35 sub-Saharan African (SSA) countries. A total weighted sample of 191,953 children under 5 years of age was included in the analysis. Descriptive and inferential analyses were performed using STATA 17. Forest plots were utilized to illustrate both pooled and country-specific stunting rates. Determinants of stunting were identified through a multilevel mixed-effects Poisson regression model with robust variance. The adjusted prevalence ratios and their 95% confidence intervals were used to assess the strength and statistical significance of associations. Result The pooled prevalence of stunting among children under 5 years of age in 35 sub-Saharan African countries was 29.89% (95% CI: 26.63, 33.14%), with the lowest level in Gabon (13.91%) and the highest in Burundi (55.80%). Being male children (aPR = 1.24, 95% CI: 1.21–1.26), being aged 12 months or older (aPR: ≥ 1.81, p < 0.01), insufficient antenatal care (ANC) visits (aPR: ≥ 1.17, p < 0.01), lack of postnatal visits(aPR = 1.03, 95% CI: 1.07, 1.05), children perceived as small or average at birth (aPR: ≥ 1.16, p < 0.01), mother without a higher education (aPR: ≥ 1.94, p < 0.01), living in a poor or average wealth household (aPR: ≥ 1.23, p < 0.01) were significant predictors of stunting. Conversely, maternal overweight (aPR = 0.81, 95% CI: 0.77–0.84) and obese mothers (aPR = 0.88, 95% CI: 0.85–0.90) were associated lower prevalence of stunting. Conclusion Study revealed significant country-level variations and rates exceeding 30% in 15 countries, signaling a major public health concern. The key individual, household and contextual factors associated with stunting in this study suggest the need for immediate actions expanding antenatal and postnatal care, promoting facility-based deliveries, enhancing maternal education, and media outreach. Long term strategies must tackle poverty, food systems, and equitable nutrition access, supported by governance and stability. A multisectoral approach integrating health, education, agriculture, WASH, and social protection ensures substantiable child growth, complemented by longitudinal research for policy coherence.